Program Pascasarjana, Fakultas Kesehatan Masyarakat, Sekolah Tinggi Ilmu Kesehatan Tamalatea Makassar - Sitti Murni Murni; Muhammad Syafar; Asrijun Juhanto (Universitas Pahlawan, 2021)
Occupational safety and health are important things that must be applied in all workplaces, both in the formal and non-formal sectors. In 2020, based on BPJS Ketenagakerjaan data, work accident cases have increased. From previously around 114,000 accident cases in 2019, to 177,000 cases of work accidents in 2020. The risk of HCV transmission after needle stick injuries containing HCV 3 - 10: 100. In 2018 the number of work accidents in Indonesia was 114,148 cases and in 2019 there were 77,295 cases. This study aims to analyze the relationship between medical solid waste treatment and the risk of work accidents. Cleaning service at Daya Makassar Regional General Hospital in 2021. This type of cross sectional study is an observational study at Daya Hospital Makassar City involving 30 respondents. This research instrument using a questionnaire. The analysis used univariate and bivariate analysis (chi-square test). The results of this study indicate that based on the characteristics of the respondents, it is found that the sexes of men and women are the same, namely 50.0% respectively, the age group of 20-29 years is 56.7%, while the lowest is the age group â‰¥ 50 years as many as 6.7 %, respondents with high school graduation education were 43.3% and the lowest was 1 (Taman DIII / PT) as much as 3.3%. Based on the results of the bivariate test, it was found that there was a relationship between length of work (p = 0.035), PPE (p = 0.003), the availability of medical waste bins (p = 0.014) in the management of medical solid waste to the risk of work accidents at RSUD Daya Kota Makassar. There is no relationship between Knowledge (p = 0.087), attitude (p = 0.261), and supervision (p = 0.531) cleaning service on the risk of work accidents when managing medical solid waste at RSUD Daya Kota Makassar. It is hoped that there will be efforts to improve understanding of cleaning services by providing training to all new cleaning services and can increase knowledge of new cleaning services, PPE should always be fully available and monitored for use, and provide media trash bins according to standards.